Mascagni’s bicentenary: the “prince of anatomists” in Pisa - Natale, Gianfranco; Lazzeri, Gloria; Matarangasi, Antuela; Ferrucci, Michela; Ruffoli, Riccardo; Soldani, Paola (Italian Journal of Anatomy and Embryology, 2015)
The bicentenary of Paolo Mascagni’s death is the occasion to celebrate an anatomist who strongly took in the spirit of the Enlightenment. Mascagni spent the first part of his life in the University of Siena, where he had many interests, including chemistry, mineralogy, agriculture, and botany. Thanks to his mentor Tabarrani, the anatomical research became his main field of studies. He won great fame with masterpieces dedicated to the first complete description and illustration of the lymphatic system and became president of the Accademia dei Fisiocritici. After meeting with that success, Mascagni conceived the idea to realize an ambitious dream of the anatomists: a complete and life-sized illustration of the human body. Nevertheless, political events delayed his purposes and upset his life. During the French occupation of Tuscany in 1799, he embraced the case of Jacobinism and had the appointment to manage education and culture in the new government of Siena. Because of the defeat of the French army, he fell into disgrace spending about eight months in prison. Finally, at the end of 1800 Mascagni was rehabilitated and left the insecure Siena to move to Pisa, where he was named professor of anatomy at the university on January 1st 1801. Again, after a few months Mascagni was politically disapproved and accused to be irreligious. The embarrassing situation was overcome with a compromise solution: the role of professor in Pisa was maintained, but Mascagni was obliged to teach anatomy in the Santa Maria Nuova Hospital in Florence. The short stay in Pisa was very prolific. Besides the anatomical lessons, and the interesting meeting with Cuvier, Mascagni was concerned with the ultimate preparation of the anatomical tables. Some reports indicate that he lived on the second floor of the historical Agostini’s Palace on the Lungarno, and in a laboratory prepared at the last floor his pupils coloured the anatomical drawings. The masterpiece was published posthumously in 1823-1831 by the Pisan printer Capurro on the initiative of Vaccà-Berlinghieri, Barzellotti and Rosini, bearing the right title of Anatomia Universa. The 44 tables represent four front and back dissection layers of the life-sized human body and several detailed viscera. The monumental work also included black and white extra tables and a Latin textbook. Art and science are in debt to Mascagni’s contribution to modern anatomy iconography.